Efeito do treino precoce com luvas abertas aderentes no aprimoramento do alcance de lactentes de baixo nível socioeconômico: ensaio clínico randomizado - Greco, Ana Luiza Righetto (Universidade Federal de São Carlos, 2020)
In the early stages of motor development, the infant develops the reaching skill. The variability of the movements of the upper limbs added to the exteroceptive stimuli are important for the improvement of this skill. However, a context of adversity can be harmful to the infant. The multiple risks associated with poverty to which infants and their families are exposed can negatively impact child development. For instance, especially in the first year of life, low socioeconomic status infants may have limitations in activities related to oral and manual exploration, cognition and attention. Since motor development is not a process that occurs in isolation, but more than that, it is related to other areas of development, limitations in early motor activities resulting from adverse environments can impact future motor and cognitive development. Thus, providing intervention strategies for at-risk infants early in life can be beneficial, since this is the most opportune time to prevent or minimize possible limitations on activities and restrictions on social participation. The application of active training protocols has been documented in the literature. Evidence points to the beneficial effects of active reaching-specific training protocols as well as sticky mittens. However, there is no consensus on the effectiveness of using sticky mittens as a strategy to improve reaching, grasping and manual exploration of objects. In an attempt to deepen in this topic and answers to conflicting questions, the present study was composed of two studies. Study 1, entitled “Active training with sticky mittens to improve reaching and manual exploration in term and at-risk infants: a systematic review”, aimed to systematically investigate the effectiveness of active training with sticky mittens to improve reaching and manual exploration in healthy full-term and at-risk infants for the motor delay. The synthesis of the evidence showed that the active training with sticky mittens to improve reaching and the manual exploration of objects presented very low evidence in infants born at term and low evidence in at-risk infants. Study 2, entitled “Effects of specific training with open sticky mittens on improving reach in low socioeconomic status infants: a randomized clinical trial”, aimed to investigate the effects of applying active training with open sticky mittens on improving the reach of low socioeconomic status infants at the age of emergency of reaching and at 6 months of chronological age. The results showed that the effectiveness of active training of specific task of reaching with open sticky mittens was not superior to social training in low socioeconomic status infants. Low socioeconomic status infants in both groups had an adequate functional pattern of reaching at six months of age, however, the performance of reaching movements was below to age. This work highlights the importance of recognizing the potential risk that poverty represents for infants living in these conditions.
Effects of early specific training with open sticky mittens to improve reaching skill in low socioeconomic status infants: a randomized clinical trial”
Keywords: Habilidade motora; Lactente; Nível socioeconômico; Desenvolvimento infantil; Infant; Motor Skill; Socioeconomic status; Child development; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL